High Speed Mobility Management Performance in a Real LTE Scenario - Abuelgasim, A. A. M. K.; Yusof, K. M. (Engineering, Technology & Applied Science Research, 2020)
This paper discusses the mobility management for high-speed users, which is a crucial challenge for all mobile operators, especially when users are moving vertically across different network technologies. Mobility, also known as seamless connectivity, is directly influencing the quality of service (QoS). Mobility management-Handover (HO) performance was evaluated by field measurements of a Long Term Evolution (LTE) network of a mobile operator in the Middle East. Drive test measurements were used to analyze the results of different high-speed scenarios. User Equipment (UE) with high speed of 80-140km/h causes a high risk of failure of seamless connectivity as the HO procedure timing is longer than for UE with smaller speed. HO failure and call drop may occur when UE is moving with high speed across two adjacent cells in highways. During measurements, HO failure occurred when UE speed was 140km/h, and HO preparation timing increased when UE speed increased.